Exploring the impact of macrophage polarization and Modic changes on baseline clinical condition in radiculopathy due to lumbar disc herniation - Wensen Li; Niek Djuric; Christiaan Mink; Carmen L.A. Vleggeert-Lankamp (Brain and Spine)
Introduction: Lumbar intervertebral disc herniation (LDH) often manifests as sciatica, resulting from mechanical compression and/or an inflammation affecting the nerve root. Research question: This study aims to investigate the impact of inflammation and macrophage polarization on clinical symptoms in surgical LDH patients. Material and methods: Nucleus pulposus (NP) tissue samples were obtained from LDH patients. Clinical symptoms were assessed using the Numerical Rating Scale (NRS) for back pain and leg pain, and the Oswestry Disability Index (ODI). HE and CD68 staining were employed to detect inflammation in the samples while CD163 and CD192 were utilized as markers for M1 and M2 macrophage phenotypes respectively. MRI was screened for Modic changes (MC). Results: A total of 187 patients were included. Inflammation was found in 140 patients, with 93 having severe inflammation. MC type I was present in only 8 % of patients (16 patients), type II in 37 %. Inflammation severity correlated with back pain (p = 0.021). M1 macrophage dominance associated with the presence of more intense back pain, especially in patients with MC type II (p = 0.001). Inflammation severity positively correlated with leg pain, but only in patients without Modic changes (p = 0.003). Discussion and conclusion: The link between back and leg pain and intervertebral disc inflammation appears to be influenced by the presence or absence of MC. These findings reveal distinct roles for M1 and M2 macrophages in clinical symptoms, warranting further investigation. Large-scale cohort studies are needed to validate and expand upon these observations.